2004
DOI: 10.1021/bi048360c
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Replication and Repair of DNA Containing a C2‘-Oxidized Abasic Site

Abstract: Abasic lesions are unable to form Watson-Crick hydrogen bonds with nucleotides. Nonetheless, polymerase and repair enzymes distinguish between various oxidized abasic lesions, as well as from nonoxidized abasic sites (AP). The C2-AP lesion is produced when DNA is exposed to gamma-radiolysis. Its effects on polymerases and repair enzymes are unknown. A recently reported method for the chemical synthesis of oligonucleotides containing C2-AP at a defined site was utilized for studying the activity of Klenow exo(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…The K m for this process is comparable to those describing AP and L incision by Ape1, but the k cat is about 30-fold slower (35). In addition, Ape1 incises C2-AP approximately 10-fold less efficiently than does Xth (8). Pol β efficiently extends the 3′-terminus of the fragment at the incision site by 2 nucleotides, or one nucleotide past the lesion, and is assisted by FEN1.…”
Section: Discussionmentioning
confidence: 98%
“…The K m for this process is comparable to those describing AP and L incision by Ape1, but the k cat is about 30-fold slower (35). In addition, Ape1 incises C2-AP approximately 10-fold less efficiently than does Xth (8). Pol β efficiently extends the 3′-terminus of the fragment at the incision site by 2 nucleotides, or one nucleotide past the lesion, and is assisted by FEN1.…”
Section: Discussionmentioning
confidence: 98%
“…Deoxyribose structures, including chemically reduced abasic sites, abasic site analogues ( e.g. , tetrahydrofuran), and sugar lesions arising from either C-1′ or C-2′ oxidation of deoxyribose that have been initially cleaved on the 5′ side by APE1 are refractory to excision by POLβ (60, 61). Since the chemical structures of these 5′-end lesions prevent β-elimination by POLβ, they will be substrates for FEN1-dependent repair by LP-BER (62).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, when a method for synthesizing oligonucleotides containing C2-AP was reported, little was known about the lesion's biochemical effects (16). Subsequent in vitro experiments revealed that C2-AP in DNA is incised by the Type II E. coli repair enzymes, exonuclease III (Exo III) and endonuclease IV (Endo IV), albeit less efficiently than other abasic lesions (17). Herein we describe the replication of templates containing the C2-AP and the role of SOS polymerases in bypassing the lesion in E. coli using single-stranded shuttle vectors.…”
mentioning
confidence: 99%